Interpreting China's development - Wang, Gungwu; Wong, John 1939- (World Scientific, 2007)
In Interpreting China's Development, leading experts on China provide an overview of this growing superpower, highlighting key issues in the country's political, economic and social development. Underpinned by up-to-date scholarly research yet written in a readable and concise style, this volume of over 40 short chapters offers a very accessible way to understanding the major events and dominant issues that had emerged in China over the last few decades. The essays are grouped under four thematic sections - challenges of governance, growth and structural changes, coping with rising social problems and relations with major powers and neighbours -covering salient topics such as the emerging mode of leadership succession, sustainability of China's high growth, widening inequalities, environmental crisis and the external impact of China's rise. Non-specialists in particular, should find this volume useful in keeping up with China's fast changing developments.